Case report: Prone positioning in the improvement of severe post-operative hypoxia following aortic dissection - Wang, Yun; Cheng, Xuping; Jiang, Xuandong; Chen, Lijun (Frontiers in Medicine, 2024)
Postoperative hypoxemia after aortic dissection surgery presents a considerable clinical challenge, and acute respiratory distress syndrome (ARDS) is a common etiology. Prone positioning treatment has emerged as a potential intervention for improving respiratory function in this context. We report the case of a 27-year-old male who developed severe hypoxemia complicated by pulmonary embo-lism after aortic dissection surgery. He was diagnosed with postoperative hypoxemia combined with pulmonary embolism following aortic dissection. His respiratory status continued to deteriorate de-spite receiving standard postoperative care, thereby necessitating an alternative approach. Implementation of prone positioning treatment led to a substantial amelioration in his oxygenation and overall respiratory health, with a consistent hemodynamic state observed throughout the treatment. This technique resulted in significant relief in symptoms and improvement in respiratory parameters, facilitating successful extubation and, ultimately, discharge. This case underlines the possible efficacy of prone positioning therapy in managing severe hypoxia complicated by pulmonary embolism following aortic dissection surgery, warranting more thorough research to explore the potential of this treatment modality.